Maxillary verrucous carcinoma coincident with cervical lymph node metastasis of colon adenocarcinoma - Kato, Hatsumi Yano; Ishibashi, Hiroaki; Nariai, Yoshiki; Hideshima, Katsumi; Vieth, Michael; Sekine, Joji (International Surgery, 2012)
Cervical lymph node metastasis is an extremely rare event in oral verrucous carcinoma. Isolated cervical lymph node metastasis of colon cancer is also rare. This article describes a case of maxillary verrucous carcinoma accompanied by colon adenocarcinoma that metastasized to a cervical lymph node in a 69-year-old Japanese woman. During preoperative evaluation for maxillary verrucous carcinoma, enlarged cervical lymph nodes and colon cancer were suspected by positron emission tomography. Colonoscopy with biopsies confirmed primary colon adenocarcinoma. Left radical neck dissection, partial maxillectomy, and full-thickness skin graft to the mucosa of the upper lip were performed before treatment of colon adenocarcinoma. Cervical lymph nodes showed metastasis from colon adenocarcinoma, and right hemicolectomy was performed. This is the first case report of synchronous oral verrucous carcinoma and colon adenocarcinoma with cervical lymph node metastasis.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Adenocarcinoma; Cervical lymph node metastasis; Double cancer; Verrucous carcinoma